English, German, and French Tourists Are Key to the Success of Andalusian Destinations (Spain). - Florido Benítez, Lázaro (MDPI, 2023)
Why was this research undertaken? Because in some tourist destinations the number of international tourists has a greater impact on the number of overnight stays at hotels compared to domestic tourism. The aim of this study was to analyse the main tourist market segments in destinations in Andalusia from 2004 to 2022, to demonstrate the relevance of, and dependency on, the tourism industry in this territory. The methodology used in this research collected secondary data from Spanish and Andalusian public organizations (IECA, INE, SAETA and AENA), and information related to this topic from researchers and organizations (primary data) to select specific indicators and to draw the appropriate conclusions. The findings of the current study reveal that English, German, French, Italian, Belgian, and American tourists are the main markets of the Andalusian provinces and their hotel establishments. In addition, these three segment markets depend on the air accessibility and connectivity provided by Andalusian airports. Moreover, it should be remembered that domestic tourism generates 35.1% of the overnight stays at Andalusian hotels. Domestic tourism helped the hoteliers of Andalusia to survive the pandemic crisis when inbound tourism dropped to zero. Andalusia constitutes an interesting case of study because it attracts a large amount of tourism demand. Although English, German, and French markets monopolize the number of overnight stays, DMOs need to attract tourists from other countries to diversify the tourism demand.
Keywords: Turismo - Andalucía; Tourists; Hotels; Airports; Accommodation; Hotel occupancy rate; Passenger arrivals; Overnight stays